Analyzing slowly exchanging protein conformations by ion mobility mass spectrometry: study of the dynamic equilibrium of prolyl oligopeptidase. (10th June 2016) - López, Abraham; Vilaseca, Marta; Madurga, Sergio; Varese, Monica; Tarragó, Teresa; Giralt, Ernest
Abstract : Ion mobility mass spectrometry (IMMS) is a biophysical technique that allows the separation of isobaric species on the basis of their size and shape. The high separation capacity, sensitivity and relatively fast time scale measurements confer IMMS great potential for the study of proteins in slow (µs–ms) conformational equilibrium in solution. However, the use of this technique for examining dynamic proteins is still not generalized. One of the major limitations is the instability of protein ions in the gas phase, which raises the question as to what extent the structures detected reflect those in solution. Here, we addressed this issue by analyzing the conformational landscape of prolyl oligopeptidase (POP) – a model of a large dynamic enzyme in the µs–ms range – by native IMMS and compared the results obtained in the gas phase with those obtained in solution. In order to interpret the experimental results, we used theoretical simulations. In addition, the stability of POP gaseous ions was explored by charge reduction and collision‐induced unfolding experiments. Our experiments disclosed two species of POP in the gas phase, which correlated well with the open and closed conformations in equilibrium in solution; moreover, a gas‐phase collapsed form of POP was also detected. Therefore, our findings not only support the potential of IMMS for the study of multiple co‐existing conformations of large proteins in slow dynamic equilibrium in solution but also stress the need for careful data analysis to avoid artifacts. Copyright © 2016 John Wiley & Sons, Ltd.